Improved criteria for sampled-data synchronization of chaotic Lur'e systems using two new approaches. (May 2017) - Lee, Tae H.; Park, Ju H.
Abstract: In this paper, the problem of the sampled-data synchronization of two identical chaotic Lur'e systems is studied in which the controller is designed by using sampled output of the systems with variable sampling rates. Two novel approaches, sampling-instant-to-present-time fragmentation and free-matrix-based time-dependent discontinuous Lyapunov approach, are proposed for the first time. The first one makes us to utilize more information of inner sampling behavior and later one helps handling a hybrid feature of sampled-data control systems. Based on the presented two new approaches, novel synchronization conditions are developed in the form of linear matrix inequalities. The obtained conditions ensure the master–slave synchronization of chaotic Lur'e systems under larger sampling period than remarkable existing works which can be found by two numerical examples.